2014
DOI: 10.1146/annurev-food-030713-092431
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Impacts of Foodborne Mycotoxins

Abstract: Mycotoxins are toxic and carcinogenic metabolites produced by fungi that colonize food crops. The most agriculturally important mycotoxins known today are aflatoxins, which cause liver cancer and have also been implicated in child growth impairment and acute toxicoses; fumonisins, which have been associated with esophageal cancer (EC) and neural tube defects (NTDs); deoxynivalenol (DON) and other trichothecenes, which are immunotoxic and cause gastroenteritis; and ochratoxin A (OTA), which has been associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
314
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(349 citation statements)
references
References 121 publications
4
314
0
6
Order By: Relevance
“…Aflatoxin contamination of many important seed crops causes enormous agricultural economic losses [35]. Several antimicrobial agents including Cu fungicides have been examined for A. flavus growth inhibition as potential post-harvest interventions [36].…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxin contamination of many important seed crops causes enormous agricultural economic losses [35]. Several antimicrobial agents including Cu fungicides have been examined for A. flavus growth inhibition as potential post-harvest interventions [36].…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxin will be released by the body through bile, milk, egg, and urine. When aflatoxin can not be excreted from the body, there will be pathological changes and cause some symptoms such as birth defects (teratogenic effects), cancer (human and animals) and the death (Wu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are attributed to risk factors such as high daily intake of aflatoxins and high incidence of hepatitis B [24]. Morevoer, mycotoxins are often related to the impairment of children' growth [14,25,26]. Very recently, it has been shown that insulin-like growth factor 1 (IGF-1) axis may represent a common causal pathway in mycotoxin effects on hepatocellular carcinoma as well as growth retardation [27].…”
Section: Adverse Effects Of Mycotoxins On Humansmentioning
confidence: 99%